Heritage-planning nexus: de/centralisation of Latvian heritage policies in the name of cultural nationalism - Rituma, Rituma (Riga Graduate School of Law, 2022)
Public discourse is filled with conceptual discussions around both regionalism-globalization and nationalism-localism nexu. With the environment being at the spotlight of these discussions, human awareness of the surroundings have doubled if not tripled. Nevertheless what sometimes gets lost in these discussions are the sense these surroundings represent – sense of place, sense of belonging, etc. Discussions around the living environment tend to mention cultural landscapes or heritage per se as a side note. This work will attempt to shed light on how institutional arrangements and regulatory framework ties our environment, our regional- and local-selves with broader concepts of cultural nationalism.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law; Cultural nationalism; Cultural heritage; The Republic of Latvia; Heritage-planning